2011
DOI: 10.1002/eji.201141592
|View full text |Cite
|
Sign up to set email alerts
|

M cells expressing the complement C5a receptor are efficient targets for mucosal vaccine delivery

Abstract: In the mucosal immune system, M cells are known as specialized epithelial cells that take up luminal antigens, although the receptors on M cells and the mechanism of antigen uptake into M cells are not well-understood. Here, we report the expression of the complement C5a receptor (C5aR) on the apical surface of M cells. C5ar mRNA expression in co-cultured Caco-2 human M-like cells was six-fold higher than in mono-cultured cells. C5aR expression was detected together with glycoprotein 2, an M-cell-specific prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 44 publications
(59 reference statements)
1
51
0
3
Order By: Relevance
“…For example, M cell-specific antibody effectively delivers the conjugated antigen into the M cells, and UEA-1 interacting with α-L-fucose on M cells is used as a delivery mediator (13). Our previous studies also suggested that M cell-targeting ligand Co1 interacts with C5aR expressed on M cells and that this interaction is related with antigen delivery and induction of antigen-specific immune response (9,10). Our study also showed that Co1-conjugated viral antigen VP1 of FMDV more effectively interacted with M cells in ileal PPs compared to VP1 alone without Co1 ligand conjugation (Fig.…”
Section: Discussionmentioning
confidence: 83%
“…For example, M cell-specific antibody effectively delivers the conjugated antigen into the M cells, and UEA-1 interacting with α-L-fucose on M cells is used as a delivery mediator (13). Our previous studies also suggested that M cell-targeting ligand Co1 interacts with C5aR expressed on M cells and that this interaction is related with antigen delivery and induction of antigen-specific immune response (9,10). Our study also showed that Co1-conjugated viral antigen VP1 of FMDV more effectively interacted with M cells in ileal PPs compared to VP1 alone without Co1 ligand conjugation (Fig.…”
Section: Discussionmentioning
confidence: 83%
“…For example, GP2, an M-cell-specific protein expressed in both human and mouse M cells, plays a receptor role by aiding the uptake of FimH + bacteria into M cells [22]. In our previous study, we showed that complement 5a receptor could function as an M-cell-targeting receptor to induce Ag-specific immune responses in mucosal and systemic compartments [23]. In this study, we suggest the role of mFPR-2 as an M-cell-targeting receptor of LL-37-conjugated Ag.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the M cell-targeting ligand Co1 was selected by biopanning a phage display library against human M-like cells, suggesting the expression of a complement 5a receptor (C5aR) on M cells that was confirmed in mouse M cells. 59, 72 Transcriptomic profiling studies also suggest that genes for glycoprotein-2 ( Gp2 ), tumor necrosis factor-α expressed-induced protein 2 ( Tnfaip2 ) and Ccl9 are expressed in mature M cells. 73, 74 In addition, recent research progress on M cells suggested three pathways for luminal antigen sampling by M cells; nonspecific endocytosis, specific receptor-mediated endocytosis and via extension of transcellular dendritic processes by Lyso DCs, which have strong phagocytic activity and antigen sampling ability (Figure 3).…”
Section: Enhancing the Efficiency Of Oral Mucosal Vaccines Via M Cellmentioning
confidence: 99%
“…61 Similarly, the infection of Y. enterocolitica is closely related with C5aR on M cells, whereas the infection of Brucella abortus depends on a cellular prion protein on M cells. 59, 67 Based on these observations, it is plausible to use M cell-specific surface markers and receptors for the effective delivery of vaccine materials into the host. For example, when the M cell-specific antibody NKM 16-2-4, which recognizes α (1, 2) fucose-containing carbohydrates, was applied to an oral vaccine model against botulinum toxin, the NKM 16-2-4 combined antigen targeted M cells with high efficiency and induced antigen-specific IgA.…”
Section: Enhancing the Efficiency Of Oral Mucosal Vaccines Via M Cellmentioning
confidence: 99%